Libya’s Foreign Policy Towards Some African Countries and the Palestinian Cause, 1973-1977, in US State Department Documents / Historical Study - Ban Sabeeh Salem (Journal of the College of Education for Girls for Humanities, 2023)
Abstract During the 1970s, the Libyan government was keen to have a political and economic role in the Arab region, especially since the region was full of events and developments that left its mark not only on the Middle East, It was headed by the October 1973 war, the issue of supporting the Palestinian armed factions and the issues of creating crises within the neighboring countries of Libya and the regional countries, in the desire of the Libyan government to top the list of the most influential countries on the course of international politics. The ambitions of Libyan leader Muammar Gaddafi were even greater, and he believed that he could play a larger and larger role. He aspires to be the leader of the Arab nation and the axis of every important event that could happen in the region by adopting a policy based on anti-Israel and foreign presence. The region, by participating in the management of crises that hit the Middle East. Libya has been keen to monitor developments in neighboring countries and regional countries, especially those which feel that they pose a threat to its national security or facilitate the process of foreign presence, so Gaddafi tried to build a regional security system in the Arab region despite the contradiction between the goals and targets of some of those countries, And tried in various ways to attract some of these governments to the ranks in all international fields, but failed to achieve this, and therefore wanted to strengthen the arsenal of military army for fear of a union may bring some Arab governments and the United States and Israel against his directions.